Constructing tradition means and myths of transmission in Western esotericism - Kilcher, Andreas B., 1963- (Aries Book Series, 2010)
The question of constructing tradition, concepts of origin, and memory as well as techniques and practices of knowledge transmission, are central for cultures in general. In esotericism, however, such questions and techniques play an outstanding role and are widely reflected upon, in its literature. Esoteric paradigms not only understand themselves in elaborated mytho-poetical narratives as bearers of "older", "hidden", "higher" knowledge. They also claim their knowledge to be of a particular origin. And they claim this knowledge has been transmitted by particular (esoteric) means, media and groups. Consequently, esotericism not only involves the construction of its own tradition; it can even be understood as a specific form of tradition and transmission. The various studies of the present voume, which contains the papers of a conference held in Tübingen in July 2007, provide an overview of the most important concepts and ways of constructing tradition in esotericism.